MANAJEMEN PENGELOLAAN BOARDING SCHOOL DALAM MENINGKATKAN PENDIDIKAN KARAKTER SANTRI DI SMP IBNU HAJAR BOARDING SCHOOL - Pujiyatno (UNISAN JURNAL, 2023)
School management has the goal of forming students who are smart, creative, have good morals, and are tough. This vision and mission cannot be realized without integration between boarding schools and schools. The type of research used by researchers is a type of qualitative research. the results of field research on Boarding School Management at the Ibnu Hajar Boarding School Middle School Jakarta, it can be concluded that: The boarding school management pattern at the Ibnu Hajar Boarding School Middle School Jakarta is an integrated management pattern between the dormitory and the school. The organizational function in the boarding school is arranged hierarchically by placing the Head of SMP Ibnu Hajar Boarding School Jakarta as the top manager who manages all managerial activities. In carrying out boarding school activities at the Ibnu Hajar Boarding School Jakarta Middle School, it has been able to run smoothly and optimally, each musyrif has carried out his role and duties properly, the asatidz have also carried out various learning activities, so as to make students active and enthusiastic in activities. The supervision carried out at the Ibnu Hajar Boarding School Jakarta Middle School is carried out periodically, starting from daily, weekly, monthly, end of semester, and end of year.